The Dynamics of Neighborhood Structural Conditions: The Effects of Concentrated Disadvantage on Homicide over Time and Space. (March 2016) - Becker, Jacob H.
Several recent spatial analyses conclude the strong positive association typically found between neighborhood concentrated disadvantage and crime in cross–sectional studies significantly differs across neighborhoods. It is possible this spatial variation is due to within–neighborhood dynamics of continuity and change, as suggested by ecological theories of neighborhood crime. Using ordinary least–squares and geographically weighted regression models, I explore the role of within–neighborhood change on the disadvantage–homicide relationship across Chicago neighborhoods and find that controlling for historical changes in disadvantage within neighborhoods reduces—but does not eliminate—spatial variation in the cross–sectional relationship. Within–neighborhood changes in concentrated disadvantage from 1970 to 2000 are positively related to homicide rates, net of the level of disadvantage in 2000. This suggests the relationship is influenced to some degree by temporal continuity or change in the neighborhood ecological structure, consistent with the dynamic conceptualization of neighborhoods inherent to ecological theories of crime like social disorganization.